Eye Movement Alterations in Post-COVID-19 Condition: A Proof-of-Concept Study - Cecilia García Cena; Mariana Campos Costa; Roque Saltarén Pazmiño; Cristina Peixoto Santos; David Gómez-Andrés; Julián Benito-León (Sensors, 2022)
There is much evidence pointing out eye movement alterations in several neurological diseases. To the best of our knowledge, this is the first video-oculography study describing potential alterations of eye movements in the post-COVID-19 condition. Visually guided saccades, memory-guided saccades, and antisaccades in horizontal axis were measured. In all visual tests, the stimulus was deployed with a gap condition. The duration of the test was between 5 and 7 min per participant. A group of <semantics>n=9</semantics> patients with the post-COVID-19 condition was included in this study. Values were compared with a group (<semantics>n=9</semantics>) of healthy volunteers whom the SARS-CoV-2 virus had not infected. Features such as centripetal and centrifugal latencies, success rates in memory saccades, antisaccades, and blinks were computed. We found that patients with the post-COVID-19 condition had eye movement alterations mainly in centripetal latency in visually guided saccades, the success rate in memory-guided saccade test, latency in antisaccades, and its standard deviation, which suggests the involvement of frontoparietal networks. Further work is required to understand these eye movements’ alterations and their functional consequences.